Pregnancy after Solid Organ Transplantation. Issue 2 (March 2018) - Kurz, Jane M.
Abstract: Purpose: To explore the reproductive decision-making process with women who were organ transplant recipients (renal, lung, & heart transplants). Study Design and Methods: Grounded theory guided data collection and analyses. Mixed methods with audiotaped telephone interviews and a written survey measuring social support were used. As social support is critical for women who are organ transplant recipients considering pregnancy, a search for disconfirming evidence for social support via a survey and interviews was included. Analyses: Verbatim responses were analyzed through the constant comparative method using open, axial, and selective coding. Trustworthiness was established through prolonged engagement, member checking, and thick descriptions. Results: Participants included 10 women who were solid organ recipients (2 lung, 1 heart, and 7 renal transplant recipients). The core theme was Wanting a child . Other themes included Getting information, Advocating, Dealing with problems, Preparing, Talking, Supporting, Coping, and Advising others . There was no evidence of a lack of social support as evaluated via the survey or interviews. Clinical Implications: This study provides new knowledge on clinical decision-making about pregnancy for women who are solid organ recipients and for healthcare professionals. Nurses can use these data to help guide women on how to obtain the most accurate information to make a personal decision about pregnancy and to develop support from their healthcare team and family. Abstract : Women who have been recipients of heart, lung, or renal transplants have a difficult decision-making process when considering pregnany. In this study, women shared their thoughts on how they decided to become pregnant, as well as the positive experiences and significant challenges they faced in beoming mothers.